Beating heart implantation of transventricular artificial cordae: How can access site selection and leaflet insertion improve mitral regurgitation correction?. (March 2022) - Di Micco, Luigi; Biffi, Benedetta; Schievano, Silvia; Boso, Daniela P.; Besola, Laura; Fiocco, Alessandro; Gerosa, Gino; Susin, Francesca M.; Colli, Andrea; Peruzzo, Paolo
Highlights: NeoChord and Harpoon are two techniques for treating mitral valve prolapse;. Numerical analysis of access site selection and leaflet insertion is carried out;. Patient-specific geometry of FED, Forma-Frusta, and Barlow prolapse are analysed;. The final restoration is affected by both scheme implantation and geometry;. Abstract: NeoChord-DS1000-System ( NC ) and The Harpoon-Mitral-Repair-System ( H-MRS ) are two trans-apical chordal implantation devices developed for the treatment of degenerative mitral valve ( MV ) regurgitation (DMR) either if as Fibroelastic-Deficiency (FED), Forma-Frusta (FF), or Barlow (B) presentation. The aim of this study is to evaluate some of the advantages and disadvantages of these two different devices by performing numerical simulation analyses focused on different transventricular access sites in all subsets of DMR presentations. By applying a novel approach for the development of patient-specific MV domains we worked out a set of numerical simulations of the artificial chordae implantation. Different leaflet insertions and ventricle access sites were investigated, and resulting contact-area ( CA ), tensioning-forces ( F ) and leaflet's stress ( LS ) were calculated. The analyses showed that: i) NC -approach maintains low LS when performed with a posterior access site and optimizes the overlap between the leaflets at the systolic peak; ii) H-MRS -system presents better results in case of a more anterior ventricular entry site; however, for FED prolapse large variation of F and LS with respect to NC -approach are found; iii) an accidental contact between artificial sutures and the anterior leaflet may occur when valve function is restored through an excessive anterior access site. Present findings set light on specific technical aspects of transapical off-pump chords implantation, either performed with NC and H-MRS systems and highlight the advantages and disadvantages proper to the two devices. Our study also paves the basis for a systematic application of computational methodology, in order to plan a patient-specific mini-invasive approach thus maximizing the outcomes.